Three-dimensional changes in the soft tissue chin after mandibular setback surgery in adult Japanese patients with skeletal class III malocclusion - Mazyad Mousa Alnasrallah; Takahiro Toriya; Kei Kuroe; Toru Kitahara; Yoshihide Mori; Ichiro Takahashi (Taylor & Francis Group, 2024)
Purpose The purpose of the present study is to improve the quality of prediction of soft tissue morphology by clarifying the relationship between the amount of three-dimensional (3-D) changes of hard tissue and the morphological differences of the soft tissue chin before and after orthognathic surgery in skeletal class III malocclusion.Materials and methods Preoperative and six-month postoperative CT was used to analyze the changes in 26 adult Japanese skeletal class III patients. The mean age was 25.5 years. Lateral cephalograms were analyzed to evaluate the initial antero-posterior jaw relationship and the changes before and after treatment. Three-D masks and bone structures were reconstructed using 3-D modelling software, and the final chin models were defined for further analysis following voxel-based registration. Correlation and linear regression analyses were performed to clarify the relationship between the movement of the soft tissue chin and the underlying bone.Results The soft tissue chin volume and surface area significantly increased after surgery. The thickness of the chin significantly increased only at pogonion and menton after surgery. Furthermore, a statistically significant correlation between the movement of soft tissue chin and underlying bone was found. Consequently, the regression model predicted the changes in soft tissue chin from the movement of the underlying bone.Conclusion Three-D analysis of the soft tissue chin revealed a significant change in response to surgical orthodontic treatment in skeletal class III adult patients, and soft tissue chin movement could be predicted by using 3-D CT data when planning orthognathic treatment.